UPAYA PEMERINTAH DAERAH KABUPATEN PASURUAN DALAM PENANGANAN DAMPAK PERTAMBANGAN - Syafaqotur Rohmah; Muhammad Bashori Muchsin; Hayat Hayat (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2017)
The rapid development of the rock mining sector does not deny the impact of mining either positive or negative due to mining activities from digging activities, production processes to distribution. Likewise with one area in Pasuruan District Jeladri Winongan District which has the potential of natural resources in the form of andesite rocks. As one of the companies that must be in the ownership of environmental documents, the implementation of mining must certainly pay attention to the rules of the environment specified. In this case local governments also play a role in the implementation of environmental management company. Based on Government Regulation No. 27 of 2012 on Environmental Permit Article 64 explains that every environmental agency at the central, provincial and district levels is obliged to conduct guidance. From the results of the research shows that the supervision effort by the Environmental Agency of Pasuruan Regency is conducted to oversee the results of the environmental management report based on the environmental management reporting data of the mining company. The conservation program is one of the efforts to control the handling of environmental impacts, including the impact of mining. Coaching efforts are targeted for companies that are required to own environmental documents but not yet own. Keywords: Policy Evaluation, Government Efforts, Environmental Impacts.